Eksistensi Yayasan Dar El Iman Dalam Mengembangkan Dakwah Salaf - Tomi Hendra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Islam is a religion of da'wah, where Islam is not hostile, does not oppress elements of human nature. One form of da'wah group that is currently developing is the Salafi group. Salafi groups refer to the fundamental principles of Islam, namely the Qur'an and Ash-Sunnah. The Salafi group is a group that refers to the traditions of the Prophet and the Salafus Salih with the jargon back to the Qur'an and the Sunnah of the Prophet in accordance with the understanding of the Companions of the Prophet and the Tabi'in. One form of Salafiyah Da'wah is by establishing a Salaf based foundation, and organizing Islamic study groups. One of the salaf-based foundations is the Dar El Iman Foundation. This study aims to describe the existence of the Dar El Iman Foundation in developing Salaf Da'wah. This study uses a type of field research with a descriptive qualitative approach. The results of this study describe the Dar el Faith Foundation is one of the existing foundations in developing Salaf Da'wah. The existence of educational institutions that it owns, continues to carry out routine da'wah activities and the presence of its mass media.